An Abbreviated Diagnostic Maneuver for Posterior Benign Positional Paroxysmal Vertigo - Michael, Pia; Oliva, Carolina Estibaliz; Nuñez, Marcia; Barraza, Cristian; Faúndez, Juan Pablo; Breinbauer, Hayo A. (Frontiers in Neurology, 2016)
Introduction: Benign paroxysmal positional vertigo secondary to canalolithiasis of the posterior semicircular canal is perhaps the most frequent cause of vertigo and dizziness. One of its properties is a high response rate to canalith repositioning maneuvers. However, delays in the diagnosis and treatment of this entity can range from days to years, depending on the setting. Here, we present an abbreviated variation of the Dix-Hallpike maneuver, which can be used to diagnose this disease. It is similar to the standard maneuver but can be performed without an examination bed/table and requires only a backed chair (a difference that we feel is very important in settings where a clinical bed/table is not readily available). Methods: A diagnostic assessment study was conducted in 163 patients who presented with vertigo or dizziness. Results: The abbreviated test had fairly good sensitivity (80%) and high specificity (95%) for diagnosing posterior benign positional paroxysmal vertigo. Discussions: This new diagnostic maneuver may serve as a screening procedure for quickly identifying this pathology. This will allow patients to be more directly treated, without requiring unnecessary referrals or full vestibular testing, and will be especially useful in primary care settings or heavily overloaded otolaryngology or neurology departments.